How do you solve #3(x + 2) > x#?

2 Answers
Apr 14, 2018

Answer:

x>-3.

Explanation:

#3(x+2) > x#
=> #3x+6 > x#
=> #3x+6-x > x-x# ; (subtract x from both sides)
=>#2x+6 > 0#
=>#2x+6-6 > 0-6#; (subtract 6 from both sides)
=> 2x > -6
now finally divide by 2 on both sides to get,
=> #x > -3#

Apr 14, 2018

Answer:

#x> -3#

Explanation:

Expand:

#3(x+2)>x -> 3x+6>x#

Get #x# on one side, then minus #6#

#3x+6>x -> 2x> -6#

Divide by #2#:

#x> -3#

Remember what we do on one side, we do to the other. Use this when doing all the steps above